“Negative affectivity distorts thinking”: a multilevel analysis of criminogenic thinking among Pakistani incarcerated offenders - Fatima, Shameem (The journal of forensic psychiatry & psychology, 2024)
The primary aim of the study was to assess the role of negative affectivity, a dynamic factor, in predicting criminogenic thinking styles after considering the roles of stable personal factors, individual and family history of crime, and cognitive functioning. A secondary objective was to assess whether first-time vs. repeat Pakistani incarcerated offenders differ on criminogenic cognitions. A sample of 205 offenders incarcerated in Pakistani prisons completed self-report measures of negative affectivity, cognitive functioning, and criminogenic cognitions. Hierarchical multiple regression analyses were calculated to test the study hypotheses. Findings revealed that negative affectivity factors, particularly fear, were more important for understanding criminogenic cognitive patterns as they explained a significantly larger variance over and above the individual variables, history factors, and cognitive functioning in criminogenic thinking. Further findings showed that repeat offenders scored consistently higher on criminogenic cognitions compared to first-time offenders. The findings highlight the importance of developing prevention programs incorporating cognitive behavior therapeutic strategies targeting negative affectivity and criminogenic cognitions among incarcerated offenders.